Clause Structure and Language Change. - Battye, Adrian (Oxford University Press, 1995)
This is a collection of previously unpublished papers on a specific topic in historical linguistics - clause structure, an issue of central importance since the pioneering work in the late 1980s by Chomsky and Pollock. The collection testifies to the recent renewal of interest in questions of diachronic syntax, a consequence of the new emphasis on comparative issues in the principles and parameters framework. Languages studied in this volume include all the major Romance and Germanic languages.